ANALISIS PENGARUH MODAL KERJA, JAM KERJA DAN LOKASI TERHADAP PENDAPATAN PEDAGANG UMKM MAKANAN DAN MINUMAN DI KYA-KYA KEMBANG JEPUN KECAMATAN PABEAN CANTIAN KOTA SURABAYA (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are an alternative for the community to earn income in the informal sector. Supported by the many MSMEs in the food and beverage sector that are developing in the city of Surabaya such as street food, restaurants, and cafes with contemporary and modern themes. This research aims to determine the effect of working capital, working hours, and location on the income of MSME food and beverage traders at Kya-Kya Kembang Jepun, Pabean Cantian District, Surabaya City. The type of research used in this research is quantitative with multiple linear regression analysis, t-test, F-test, and correlation analysis of determination with the method of distributing questionnaires to MSME traders in Kya-Kya Kembang Jepun. The population in this study was 33 traders and the sample used was 33 respondents or all MSME food and beverage traders using a saturated sampling technique. The variables in this study consist of the independent variable (X), namely working capital, working hours, and location, and the dependent variable (Y) merchant income. The results of this study prove that working capital and location partially have a positive and significant effect on the income of MSME food and beverage traders at Kya-Kya Kembang Jepun, Pabean Cantian District, Surabaya City, but working hours partially do not have a positive and significant effect on trader income. Food and drink MSMEs in Kya-Kya Kembang Jepun, Cantian Customs District, Surabaya City. And the results of the F test prove that working capital, working hours, and location simultaneously have a significant influence on the income of food and beverage MSMEs in Kya-Kya Kembang Jepun, Pabean Cantian District, Surabaya City by 0.00<0.05 with F-count value of 53.613 >2.922 so that it can be interpreted that working capital, working hours and location have a simultaneous influence on the income of MSME food and beverage traders in Kya-Kya Kembang Jepun, Cantian Pabean District, Surabaya City.